Leadership Styles And Work-Related Attitudes Among Social Services Employees In Penang - Asaari, Muhammad Hasmi Abu Hassan; Desa, Nasina Mat; Rejab, Siti Rahayu (Future Academy, 2019)
This study intends to unearth the relationships and the impacts between leadership styles and work-related attitudes among the social services employees in Penang. The leadership styles have been identified as a major factor in determining the success or failure of organizations. This also has been associated with the behavior of the leaders in manning the employees toward the organizations' vision, mission, and goals. Moreover, the leadership styles had been associated with the employees’ performance. In this context, the employees’ workrelated attitudes, namely job satisfaction, career satisfaction, and organizational commitment. The employees of social services department had been identified for this study. They were given a self-administered questionnaire in getting their insight on their work-related attitude concerning the leadership styles of their superiors. Thus, the study employed the study tools of Leadership Development Behavior Questionnaire (Form XII), job satisfaction, career satisfaction, and organizational commitment. This study discovered the implications between leaders’ leadership styles on employees’ work-related attitudes.